PENGARUH BEBAN PAJAK TANGGUHAN, PERENCANAAN PAJAK, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN: Studi Empiris Pada Perusahaan Sektor Barang dan Konsumsi Yang Terdaftar di Bursa Efek Indonesia - Nia Safitri; Mohamad Safii (Gapenas Publisher, 2022)
Company value is an investor's perception of the company's value associated with the stock price. This research was conducted with the aim of testing and analyzing the effect of deferred tax burdens, tax planning, and dividend policies on the value of the company. This research is a quantitative approach and secondary data from goods &consumption sector companies listed on the Indonesia Stock Exchange in 2016-2021. Sampling was used using purposive sampling by obtaining 84 sample data from 14 companies that met the criteria. Using multiple regression analysis, data testing was assisted by using Eviews version 9 software. The result of this study is that the deferred tax burden has a significant influence on the value of the company, while tax planning and dividend policy have no influence on the value of the company. However, simultaneously (together) deferred tax burdens, tax planning, and dividend policies affect the value of the company